Regional economic impacts of natural resources: the case of petroleum, and forestry and logging in Sarawak - Utit, Chakrin; Saari, M. Yusof; Abd Rahman, Muhammad Daaniyall; Habibullah, Muzafar Shah; Norazman, Umi Zakiah (UNIMAS, 2020)
Extraction of natural resources has created significant contribution to the Malaysian economy as a whole. However, the growth and development of the industry do not necessarily bring considerable economic linkages to the local economy where the industry is located, thus fail to contribute to the welfare of local households. This paper validates this claim by examining the economic impacts of Crude Oil and Natural Gas; Petroleum Refinery; and Forestry and Logging industries on the state of Sarawak. For an empirical analysis, a regional input-output model that developed by using a so-called Simple Location Quotient technique, is used as the main methodology in this study. Results are consistent with our claim that the three industries show significant impacts on growth that measured by value added. However, socio-economic impacts that measured by employment are considerably low. The lower employment impacts can be supported by the two stylized facts. First, the extraction of natural resources is capital-intensive production. The activity requires skilled workers, which might be one of the factors contributing to lower income and job opportunities. Second, the industries are highly dependent on inputs from other states and from abroad, which eventually creates lower economic spill over effects within the state economy.